Acute respiratory flow restriction affects average power, but not heart rate and subjective perceived exertion in healthy women - Rousseau Silva da Veiga; Camila Borges Müller; Gustavo Dias Ferreira; Eraldo dos Santos Pinheiro; Fabrício Boscolo Del Vecchio (Colégio Brasileiro de Ciências do Esporte, 2021)
ABSTRACT This study aims to verify the effect of the restriction of the ventilatory flow on HR, RPE, and power during HIT-test performed by healthy women. The participants (n=8) underwent HIT-test without and with ventilatory flow restriction. HR, power, and RPE was measured. HRpost showed no significant difference between conditions (p=0,053). The average power presented higher values in the condition without the restriction of ventilatory flow (619,51±144,33W; 565,99±108,43W; p=0,001), but without differences in the fatigue index (p=0,383). In both conditions, increases in RPE were observed during the efforts (p<0,001). It is concluded that HR and RPE did not suffer acute effects from the restriction of ventilatory flow; however, the average power is decreased during HIT-test.